(untitled) (Colombia Medica, 2021)
Case description: Case of Lipemia Retinalis (Lipemia Retinalis ) secondary to hyperchylomicronemia in a 40-year-old man with a history of total body irradiation and immunosuppressive treatment came to the hospital due to decreased visual acuity and abdominal pain. Clinical findings: Hyperchylomicronemia caused the development of acute pancreatitis and Lipemia Retinitis . The last one is an infrequent ocular manifestation that reflects excessive triglyceride parameters in the organism (> 2.000 mg / dL). Lipemia Retinalis is the accumulation of chylomicrons in the retinal vessels, which gives them a white and creamy appearance in direct retinal ophthalmoscopy. The initial clinical suspicion of hyperchylomicronemia was based on the visualization of the supernatant in the analytical tube. Treatment and result: Without having definitive biochemical results, due to the need for special processing of the sample, lipid-lowering treatment and serum therapy were established after the ophthalmological confirmation of Lipemia Retinalis, with full recovery of visual acuity. Clinical relevance: Given the initial difficulty in this kind of patient to determine the accurate triglyceride levels, early visualization of milky-colored retinal vessels on a salmon-colored fundus can help develop an early clinical suspicion of severe hyperchylomicronemia and contribute to limit the severity of complications.